OEE Implementation On Safety Helmet Plastic Injection Process - Chua, Yun Chin (2021)
Quote above implies how significant this research is in the digital transformation of industry along with Internet of Things (IoT). Data collection is the first and foremost step to achieve continuous improvement (kaizhen) with the utilization of data analytics. This research focused on the implementation of Overall Equipment Effectiveness (OEE) in safety helmet plastic injection process at Proguard Technologies (M) Sdn Bhd. In this paper, OEE computation will be demonstrated on real cases by using Microsoft Excel. Besides, it will reveal the methodology of developing an automatic data acquisition system with IoT capability to collect the data required to perform OEE analysis. By implementing the solution proposed in this paper, Proguard Technologies (M) Sdn Bhd is expected to reduce at least 80% time spent for data collection process. Not only that, the proposed solution also offers many additional features such as cloud monitoring, data analytics, self-triggered call alert, auto-generated email as well as live OEE dashboard.